KAJIAN POSMODERNISME: FENOMENA FOTOGRAFI MAKANAN DALAM MEDIA SOSIAL INSTAGRAM (STUDI KASUS TERHADAP GENERASI Z) - Asmawati; Ardianti Dwi Andini; Hasrafiah Agung; Asnira Sainuddin (STKIP Subang, 2026)
The development of social media has significantly influenced changes in communication patterns and lifestyles, particularly among Generation Z. One of the emerging phenomena is food photography on Instagram, which functions not only as documentation but also as part of a digital lifestyle. This study aims to examine Generation Z’s perceptions of food photography on Instagram in relation to lifestyle, consumption, and social media influence. This research employs a quantitative approach with a descriptive method. Data were collected through a Google Form questionnaire distributed to 50 Generation Z respondents who are active Instagram users. The research instrument used a five-point Likert scale, consisting of strongly agree, agree, neutral, disagree, and strongly disagree. Data analysis was conducted using descriptive techniques by calculating the frequency and percentage of respondents’ answers. The findings show that food photography on Instagram is perceived by most respondents as part of a modern lifestyle. The phenomenon is also considered to contain consumptive elements and is able to influence respondents’ perceptions and consumption experiences. However, social media influence is not dominant across all respondents, as variations in attitudes were found in each indicator.